Intestinal T‐cell lymphoma with enteropathy‐associated T‐cell lymphoma‐like features arising in the setting of adult autoimmune enteropathy. Issue 2 (14th February 2018) - Ciccocioppo, Rachele; Croci, Giorgio A.; Biagi, Federico; Vanoli, Alessandro; Alvisi, Costanza; Cavenaghi, Giorgio; Riboni, Roberta; Arra, Mariarosa; Gobbi, Paolo G.; Paulli, Marco; Corazza, Gino R.
Abstract: Enteropathy‐associated T‐cell lymphoma is regarded as a dismal, late complication of coeliac disease, though a single case of T‐cell lymphoma with such features arising in the setting of autoimmune enteropathy of the adult has been reported to date. We aim to describe the case of a 41‐year‐old woman complaining of severe malabsorption syndrome, who was diagnosed with autoimmune enteropathy based on the presence of flat intestinal mucosa unresponsive to any dietary restriction and positivity for enterocyte autoantibodies. Steroid therapy led to a complete recovery of both mucosal and clinical findings over 12 years, when disease relapse was accompanied by the appearance of monoclonal rearrangement of T‐cell receptor‐γ and peculiar T‐cell phenotypic abnormalities, leading to a rapid transition to an overt T‐cell lymphoma with features of the enteropathy‐associated subtype. Despite intensive treatment, the patient developed cerebral metastasis and died 9 months later. Our case enhances the concept of enteropathy‐associated T‐cell lymphoma as a disease that may arise in the setting of enteropathies other than coeliac disease, thus representing a heterogeneous entity. Moreover, our observations support the need of a close follow‐up of these patients, coupled with comprehensive characterization of mucosal biopsies.